2011
DOI: 10.1038/ejcn.2011.3
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study on nutritional risk factors in non-alcoholic fatty liver disease in Indian population

Abstract: Background/Objectives: Non-alcoholic fatty liver disease (NAFLD) is considered an integral part of metabolic syndrome (MS). We aimed to explore the inter-relations of MS and dietary composition in subjects with and without hepatic steatosis and to identify the nutritional risk factors contributing to NAFLD. Subjects/Methods: In all 98 subjects with steatosis and 102 controls were selected for the study after screening 260 consecutive healthy individuals. Anthropometric and nutritional information, biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 26 publications
4
18
0
2
Order By: Relevance
“…A similar study done in India compared the dietary intakes of 98 patients with that of 102 healthy controls through another semiquantitative FFQ and showed that the percentage of fat in the diet was a risk factor for the development of NAFLD. 20 Contrary to that, a US-based study of 74 patients undergoing bariatric surgery revealed that increased carbohydrate intake (measured through 24-h FR) was associated with increased odds of intrahepatic inflammation, whereas increased fat intake decreased the odds of inflammation. 21 Total caloric and protein intake were not associated with liver biopsy results in this study.…”
mentioning
confidence: 89%
“…A similar study done in India compared the dietary intakes of 98 patients with that of 102 healthy controls through another semiquantitative FFQ and showed that the percentage of fat in the diet was a risk factor for the development of NAFLD. 20 Contrary to that, a US-based study of 74 patients undergoing bariatric surgery revealed that increased carbohydrate intake (measured through 24-h FR) was associated with increased odds of intrahepatic inflammation, whereas increased fat intake decreased the odds of inflammation. 21 Total caloric and protein intake were not associated with liver biopsy results in this study.…”
mentioning
confidence: 89%
“…Patients with NALFD are shown to have increased percentage of dietary fat content and also get much lower percentage of their calories from fruits [23, 24]; not only total fat content in the diet but also the composition of fat has seen considerable interest in recent times. Current literature supports the fact that diet of patients with NAFLD might be high in saturated fatty acids and n-6 polyunsaturated fatty acids and low in n-3 polyunsaturated fatty acids and monounsaturated fatty acids [25–27].…”
Section: Factors Contributing To Development Of Obesitymentioning
confidence: 99%
“…Studies examining the dietary habits of patients with NAFLD when compared with healthier controls have reported various patterns. Notable dietary trends have included higher energy intake, 65,66 lower total dietary fiber, 67,68 higher CHOs, 65,[69][70][71] higher saturated fatty acids and cholesterol, 67 low PUFAs, 67,69,72 higher n-6:n-3 ratios, 68 higher fructose, 69,73 and higher protein from meat sources. 73 Results are therefore somewhat disparate, and not unexpectedly, ethnicity would appear to have some influence (e.g., higher CHO intakes seen mostly among Asian and Continental regions); dietary patterns, and thus their nutrient content, vary considerably across different areas and populations of the world.…”
Section: Calorie Restriction For Weight Lossmentioning
confidence: 99%